Analisis Indikator Makro Ekonomi Terhadap Nilai Tukar Petani Maluku Utara: Studi Kasus Subsektor Perkebunan Rakyat - Prince Charles Heston Runtunuwu (Society, 2020)
This study aims to determine the effect of production, land area, and labor on the Farmer Exchange Rate of the smallholder plantation crops subsector individually or partially and the effect of production, land area, and labor simultaneously on the Farmer Exchange Rate in North Maluku Province in 2014 -2018. The object of this study was the farmers of North Maluku Province because the agricultural sector plays an important role and contributes greatly to the economy in North Maluku Province. This study was conducted in January-May 2020. The data collected and processed in this study are data within 5 years. The population in this study was all data on the Farmer Exchange Rate, agricultural production, agricultural land area, and labor in North Maluku Province in 2014-2018. The data used in this study were secondary data obtained from the Central Agency on Statistics of North Maluku Province in 2020 and other literature related to this study. The test tool used is multiple linear regression analysis, and the analytical tool used was IBM SPSS Statistics 16.0 software. The results showed that partially production did not affect the Farmer Exchange Rate of smallholder plantation crops in North Maluku province. Partially, land areas affect the Farmer Exchange Rate of smallholder plantation crops in North Maluku province. Individually or partially, the labor did not affect the Farmer Exchange Rate of smallholder plantation crops in North Maluku province. Simultaneously or overall, production, land area, and labor affect the Farmer Exchange Rate of smallholder plantation crops in North Maluku province, it can be said that it will affect the farmer welfare.